On the social value of public sculpture design in Small And Medium-Sized cities in the new era. - Lan, Wu; Ai Peng, Foo (Journal of Islamic, Social, Economics and Development, 2025)
In the new era, the art design of public sculpture in small and medium-sized cities has unique social significance and aesthetic value. However, at present, the public sculpture design in small and medium-sized cities in China is facing some problems, such as the lack of systematic planning, the poor management, the fault effect of publicity and promotion, and insufficient financial assistance. To effectively promote the development of small and medium-sized cities, it is necessary to continuously strengthen urban planning, improve the overall layout, continue to provide legal support, strengthen urban supervision, strengthen publicity, build a coordinated communication mechanism, enhance financial security, and build stable investment channels.